Birds and endemism in relict forests on western slopes of the North Peruvian and South Ecuadorian Andes - Flanagan, Jeremy N. M. (2005)
The relict forests of the west slopes of the Andes of northern Peru and southern Ecuador form part of the Tumbesian Endemic Bird Area (characterized by dry forests) and at higher altitudes the Southern Central Andes Endemic Bird Area (characterized by cloud forests and paramo). The Tumbesian Region is recognized for its high level of endemic birds, many of which are threatened and also for the high level of deforestation and fragmentation of its natural habitats. This article presents an overview of the state of conservation of these birds and forests, with recommendations for improving the conservation of the last forests of the western slope.